2015
DOI: 10.1177/0267659115584418
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized versus conventional cardiopulmonary bypass and acute kidney injury after cardiac surgery

Abstract: The MCPB system is not associated with a lower incidence of AKI in Asian patients undergoing CABG. Risk factors for AKI differed between patients using the MCPB and CCPB systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Up to date, few RCTs have systematically compared the incidence of AKI following CABG using AKIN classification. 7,23 In accordance with our findings, both studies could not demonstrate any significant difference in the incidence of AKI in low risk CABG patients.…”
Section: Discussionsupporting
confidence: 91%
“…Up to date, few RCTs have systematically compared the incidence of AKI following CABG using AKIN classification. 7,23 In accordance with our findings, both studies could not demonstrate any significant difference in the incidence of AKI in low risk CABG patients.…”
Section: Discussionsupporting
confidence: 91%
“…Initially, the miniaturized cardiopulmonary bypass (MCPB) systems have been developed to render on-pump cardiac surgeries more efficient and the preliminary reported incidence of AKI was lower in patients that had MCPB than those with conventional CPB (29% vs. 41%) [45] . However, in the study by Chew et al [46] , they have identified similar rates of AKI in both cohorts and thus the superiority of either technique remains debatable [46] .…”
Section: Akinmentioning
confidence: 99%
“…Acute kidney injury (AKI) following elective coronary artery bypass graft (CABG) surgery occurs up to 45% of patients and it is associated with increased medium-and long-term cardiovascular morbidity and mortality [1][2][3][4][5]. AKI after CABG has been attributed to reduced renal blood flow by cardiopulmonary bypass [6,7] and hemodynamic instability. Contrast agent, regularly used in percutaneous coronary intervention (PCI) [8][9][10], may also contribute to the risk of postoperative AKI in CABG patients undergoing pre-surgery coronary angiography [11][12][13].…”
Section: Introductionmentioning
confidence: 99%